The Role of [BF4]− and [B(CN)4]− Anions in the Ionothermal Synthesis of Chalcogenidometalates. Issue 14 (25th January 2018) - Santner, Silke; Sprenger, Jan A. P.; Finze, Maik; Dehnen, Stefanie
Abstract: The role of borate anions in ionothermal syntheses of crystalline chalcogenidometalates was shown by the directed ionothermal synthesis of seven new selenidostannates in ionic liquids with either [BF4 ] − or [B(CN)4 ] − anions. Single crystal structures are presented of four compounds, (C4 C1 C1 Im)5 [Sn9 Se20 ][BF4 ] (1, Im=imidazolium), (DMMPH)4 [Sn2 Se6 ] (2, DMMP=2, 6‐dimethylmorpholine), (C2 C1 Im)2 (DMMPH)2 [Sn6 Se14 ] (3 ), and K2 [Sn3 Se7 ] (4 ), and how the chosen ionic liquid anion, and the reaction temperature, influences the product spectrum is discussed: Notably, 1 contains an entire formula unit of the ionic liquid, (C4 C1 C1 Im)[BF4 ], while4 contains neither the cation nor the anion of the ionic liquid—both observations being very uncommon for ionothermal syntheses. Three further compounds were obtained that exhibit strong disorder in the crystal structures (I ‐III ), for which only their anionic substructures are discussed herein. Compound4 andI‐III are based on the same layered selenidostannate substructure, 2D‐{[Sn3 Se7 ] 2− }, yet with different inter‐layer distances, which is clearly reflected in the crystal colors and quantitative optical absorption properties. Abstract : New selenidostannates were synthesized in ionic liquids with either [BF4 ] − or [B(CN)4 ] − anions. The choice of the anion and the reaction temperature notably affect the product spectrum, which comprises very uncommon compounds, and indirectly also the optical absorption properties.